(untitled) (Fiep Bulletin - online, 2011)
Proposals for actions developed for Camps in Early Childhood Education Units (UEI) "Cremation" and "St. Augustine" in the months of January and July, to promote recreational activities, focusing on the games, where children can have momentsspontaneity, relaxation and interaction between her emotional and social aspects of developing and contributing to the construction of the learning process. To produce these shares will be offered to children playing activities, games, games, toys sung, bowling balls, pool, park, fishing, storytelling, songs and dances. Experiences considering the movement of different languages, with language as driving, playing.Thus, interactions between the subjects included in the learning process will be and therefore the full development of these children.